2019
DOI: 10.1093/chemse/bjz059
|View full text |Cite|
|
Sign up to set email alerts
|

Sequence-Based Prediction of Olfactory Receptor Responses

Abstract: Computational prediction of how strongly an olfactory receptor (OR) responds to various odors can help in bridging the widening gap between the large number of receptors that have been sequenced and the small number of experiments measuring their responses. Previous efforts in this area have predicted the responses of a receptor to some odors, using the known responses of the same receptor to other odors. Here, we present a method to predict the responses of a receptor without any known responses by using avai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 76 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…Using an empirical approach described in ( Chepurwar et al., 2019 ), we identified the top 20 amino acid positions that predict the odorant responses of ORs. These amino acid positions were determined using the response data from the OR22a receptors across 14 Drosophila species for which genomic sequence data were available ( Figures 5 and S5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Using an empirical approach described in ( Chepurwar et al., 2019 ), we identified the top 20 amino acid positions that predict the odorant responses of ORs. These amino acid positions were determined using the response data from the OR22a receptors across 14 Drosophila species for which genomic sequence data were available ( Figures 5 and S5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to predict OR responses to odorants have also achieved encouraging results. 17 20 However, data scarcity in the immense odor space is a major bottleneck for good predictivities. To date, less than 50% of human ORs (hORs) and 20% of mouse ORs (mORs) have been deorphanized with less than 250 odorants ( Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on insect and mammalian ORs demonstrated that selecting subsets of 20 residues could indeed increase the model predictivity. 20 However, if one assumes that a given function is mostly encoded by 20 residues out of a GPCR sequence of ∼300 residues, the binomial coefficient [300!/20! (300 – 20)!]…”
Section: Introductionmentioning
confidence: 99%
“…Having all this data in one place, in a structured format, can enable systematic large-scale analyses to discover trends that cannot be seen with individual studies in a variety of animal models ( Crasto et al., 2002 ; Liu et al., 2004 , 2011 ; Marenco et al., 2016 ; Olender et al., 2013 ). The Database of Odorant Responses (DoOR) catalogs the OR responses of different odors in Drosophila melanogaster ( Galizia et al., 2010 ; Münch and Galizia, 2016 ) and has proved to be very useful in enabling large-scale computational analyses ( Chepurwar et al., 2019 ; Dasgupta et al., 2018 ; Saberi and Seyed-Allaei, 2016 ; Zwicker et al., 2016 ). However, no such curated dataset is available for mosquitoes.…”
Section: Introductionmentioning
confidence: 99%